Catastrophic Prosthetic Valve Endocarditis Caused by Rare Black Fungi. (30th September 2018) - Butt, Khurram; Kumar, Ranjeet; D'Souza, Jason; Limback, Joseph; Shah, Rajesh; Burt, Jeremy
Abstract : Fungal infection of prosthetic heart valves is rare and can lead to severe complications including death. Dematiaceous mold, also known as "black fungi, " are an extremely rare cause of endocarditis that usually affect immunocompromised hosts. The infection is usually chronic and can lead to heart failure and embolic complications. These fungi have limited antifungal treatment modalities. We present a rare case of prosthetic aortic valve, root, and graft infection in an immunocompetent host that revealed itself through renal, mesenteric, and cerebral embolic phenomenon. The patient underwent removal and replacement of the aortic graft followed by small bowel resection for mesenteric infarction. Patient had a successful postoperative course and underwent a long-term antifungal treatment with amphotericin B and voriconazole.